Families. - Day-Sclater, Shelley (London : Hodder & Stoughton Educational, 1999)
Family is the most popular area on the sociology syllabus, and is often the first topic studied. This book introduces the sociology student to various meanings of 'family' in current society.
Keywords: Family; Family and Relationships